(untitled) (Bangladesh Journal of Urology, 2026)
Background: Urolithiasis affects 1–15% of the global population, with management influenced by stone size and location. Percutaneous Nephrolithotomy (PCNL) is the gold standard for treating large or complex renal stones. Traditionally performed in the prone position for optimal access, prone PCNL poses challenges such as patient repositioning, anesthetic limitations, and increased risk in specific populations. Supine PCNL, introduced in 1987, offers advantages like improved ergonomics, anesthetic control, and reduced complications, but its adoption remains limited due to technical concerns and a learning curve. Aim of the study: This study aims to compare the outcome of supine and prone PCNL based on operating time, fluoroscopy time, stone free rates and postoperative complications in a tertiary care hospital in Bangladesh. Methods: This prospective, observational cohort study was conducted over one year from 1st January to 31st December, 2024 at the Department of Urology, Mugda Medical College and Hospital, Dhaka, to compare outcomes of supine (Group A) versus prone (Group B) percutaneous nephrolithotomy (PCNL) in 50 adult patients with renal stones. Patients were assigned to each group based on clinical condition and surgeon discretion. Data were collected preoperatively, intraoperatively, and postoperatively, including demographics, stone characteristics, operative details, and complications. Primary outcomes were operative time, complications (Clavien-Dindo), stone-free rate, and hospital stay. Secondary outcomes included blood loss, postoperative fever, and residual stones. Result: The study included two groups with similar baseline characteristics in age (42.6±11.4 vs. 45.8±10.7 years; p=0.28), sex (p=0.76), BMI (25.9±3.5 vs. 26.4±3.2 kg/m²; p=0.54), comorbidities, stone size (17.8±4.6 vs. 19.1±5.2 mm; p=0.31), and burden (290.5±95.6 vs. 312.3±101.2 mm²; p=0.42). Operative time was significantly shorter in the supine group (72.4±13.7 vs. 84.2±14.5 min; p=0.01). Other parameters, including fluoroscopy time, complication rates, stone-free rate (84% vs. 76%; p=0.47), and hospital stay (3.4±1.0 vs. 3.8±1.2 days; p=0.17), were comparable. No significant differences were observed in postoperative outcomes, including readmission (4% in both) and need for further procedures (8% vs. 12%; p=0.63). Conclusion: This study concludes that supine and prone PCNL are safe and effective for renal stone management. However, the supine approach offers shorter operative time and anesthesia advantages, making it preferable for high-risk patients. Choice of position should be individualized based on patient needs, surgeon experience, and institutional practices. Bangladesh J. Urol. 2025; 28(2): 71-78